Proteins and amino acids: The repair blocks and their place in growth and recovery - Rodriguez, N.R.; Lunn, W. (Nutrient Timing: Metabolic Optimization for Health, Performance, and Recovery, 2011)
Keywords: dept.hms

Potential impact of a 500-mL water bolus and body mass on plasma osmolality dilution - Sollanek, Kurt J.; Kenefick, Robert W.; Cheuvront, Samuel N.; Axtell, Robert S. (European Journal of Applied Physiology, 2011)
A methodological discrepancy exists in the hydration assessment literature regarding the establishment of euhydration, as some investigations utilize a prehydration technique, while others do not (overnight fluid/food fast). However, the degree that plasma osmolality (Posm) dilutes when using the pre-hydration method and how body mass/composition might influence the results is not known. Thirty subjects (22 M, 8 F; 20 ± 2 years (mean ± SD); 1.8 ± 0.1 m; 75.8 ± 13.5 kg) had P osm measured after an 8-h food and fluid fast (overnight fast) and 90 min after a 500-mL (4-9 mL/kg) water bolus (prehydration). From pre- to post-bolus, participants' P osm declined from 297 ± 3.5 to 295 ± 3.8 mmol/kg (p<0.05; Δ -1.7 ± 3.5 mmol/kg). One-third of the sample diluted to more than -3 mmol/kg. The effect of body mass on P osm dilution was investigated by comparing dilution in the ten lightest (62.8 ± 3.4 kg) and heaviest (92.0 ± 9.8 kg) participants; however, the change between the light (Δ -1.9 ± 3.8 mmol/kg) versus heavy groups (Δ -1.1 ± 3.0 mmol/kg) was not different (p>0.05). The correlation between body mass or total body water and change in P osm was weak (p>0.05), as was the correlation between relative fluid intake based on mass and change in P osm (p>0.05). The two methodologies appear to produce similar P osm values when measured in most individuals. However, the potential for significant dilution (>3 mmol/kg) should be considered when choosing the pre-hydration methodology. © Springer-Verlag (outside the USA) 2011.
Keywords: Adolescent; Adult; Blood; Blood Chemical Analysis; Body Weight; Dehydration; Drinking; Female; Fluid intake; Humans; Hydration assessment; Hypohydration; Male; Osmolar Concentration; SCSU-student; Total body water; Water; Water-Electrolyte Balance; Young Adult; adolescent; adult; article; blood; blood analysis; body weight; clinical trial; dehydration; dept.hms; drinking; drug effect; electrolyte balance; female; human; male; metabolism; osmolarity; physiology; water

Impaired autonomic function in normotensive obese children - Latchman, Peter L; Mathur, Madhu; Bartels, Matthew N; Axtell, Robert S; Meersman, Ronald E De (Clinical Autonomic Research, 2011)
Purpose To evaluate baroreflex sensitivity and autonomic control in a cohort of normotensive obese (OB) children. Method A cross-sectional investigation, in which, baroreflex sensitivity and autonomic control were evaluated using transfer function and power spectral density analysis (PSDA) of the electrocardiogram and beat-to-beat blood pressures in normotensive OB children and normal weight normotensive controls. All methods used were noninvasive and data were captured while seated and at rest. Results The OB and control subjects non-obese (NO) were of similar age (OB 9.1 ± 1.9 years vs.NO9.2 ± 1.4 years). The OB group was classified as having a BMI greater than the 95th percentile adjusted for age and gender, and a NO group with a BMI at or less than the 95th percentile (BMI percentile OB. 97.5 ± 1.3 vs. NO 58.5 ± 24.1). Both groups had similar normotensive blood pressures. T tests revealed that baroreflex sensitivity and HFRR were significantly reduced in the OB 9.2 ± 2.7 vs. 15.2 ± 4.7 (ms/mmHg) and 6.7 ± 1.1 vs. 8.2 ± 1.1 ms 2, respectively, while LF SBP and LF/HF ratio were significantly increased in the OB 11.9 ± 5.6 vs. 8.2 ± 4.7 mmHg 2 and 1.2 ± 0.7 vs. 0.54 ± 0.3, respectively. Conclusions Normotensive OB children exhibited significantly reduced baroreflex sensitivity, parasympathetic control as well as increased sympathetic control when compared with healthy, NO controls. Findings in this investigation raise the awareness that autonomic dysfunction is present in young OB normotensive children. © Springer-Verlag 2011.
Keywords: Autonomic Nervous System; Autonomic modulation; Baroreflex sensitivity; Blood Pressure; Child; Cross-Sectional Studies; Female; Humans; Male; Normotensive; Obese children; Obesity; article; autonomic dysfunction; blood pressure; blood pressure measurement; body mass; body weight; child; clinical article; controlled study; dept.hms; electrocardiogram; female; human; male; obesity; pressoreceptor reflex; school child; sensitivity analysis